Differentiated services in an integrated broadband network - Chen, Zhao (University of Ottawa (Canada), 2004)
This thesis evaluates the Differentiated Services (diffserv) mechanism proposed by IETF to provide QoS and resource reservation under bursty web traffic. Particularly, the performance of Weighted Fair Queuing (WFQ) algorithm is studied, using two-node and multiple link network configuration. A self-similar realistic web workload model generating aggregation of web-accessing traffic flows is developed and used to evaluate the performance, as well as other multimedia applications. Our analysis reveals that due to the burstiness of web traffic, diffserv cannot achieve all the desired QoS guarantees, especially packet delay and jitter. Three mainstream multimedia applications are modeled and analyzed in the Diffserv network with our realistic web traffic model as background traffic. Finally, our performance analysis also demonstrates that in more realistic network environment, only bi-directional resource reservation can provide to the customers QoS guarantees in Diffserv network. Several scenarios of aggregations of applications traffic flows are used to evaluate the performance, such as short-lived web traffic and non-adaptive UDP traffic.
Keywords: Engineering, Electronics and Electrical.